2022
DOI: 10.14260/jemds/2022/110
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Study to Evaluate the Efficacy of Platelet Rich Plasma, Intralesional Triamcinolone Acetonide and Intralesional Normal Saline in Moderate to Severe Alopecia Areata

Abstract: BACKGROUND Alopecia areata (AA) is a common, chronic, autoimmune, inflammatory disease that causes non scarring hair loss. Treatment of moderate to severe AA is challenging without a definitive cure. This study was undertaken to compare the efficacy of platelet rich plasma (PRP) - a novel procedural therapy, intralesional triamcinolone acetonide (ILS) and intralesional normal saline (NS) in moderate to severe AA. METHODS A total of 75 patients clinically diagnosed with Alopecia Areata were en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…8 Unal et al reported the mean age of patients of alopecia areata in their study as 27.4±9.2 years. 9 Similarly, Kapoor et al in their study reported mean age of 27.1±7.08 years. 10 In this study, males outnumbered females in terms of prevalence of AA.…”
Section: Assessmentmentioning
confidence: 74%
“…8 Unal et al reported the mean age of patients of alopecia areata in their study as 27.4±9.2 years. 9 Similarly, Kapoor et al in their study reported mean age of 27.1±7.08 years. 10 In this study, males outnumbered females in terms of prevalence of AA.…”
Section: Assessmentmentioning
confidence: 74%